Recurrent catamenial pneumothorax. Case report - Reyna-Villasmil, Eduardo (2020)
Catamenial pneumothorax is a rare and complex clinical condition that should be considered as a cause of spontaneous and recurrent pneumothorax that is often misdiagnosed. It is a pulmonary pathology commonly associated with menstruation since it occurs within 72 hours before or after the onset of menstrual bleeding. The etiology and the exact underlying mechanism have not been identified, but it could be a rare form of extra-pelvic endometriosis characterized by the presence of functional endometrial tissue in the pleura, pulmonary parenchyma, and respiratorytract. Diagnosis is a challenge, so it can result in recurrences. It should be suspected in young women of childbearing age. The first line of treatment is medical, while surgical treatment is necessary to avoid recurrence. A case of recurrent catamenial pneumothorax is presented.